Sales Pipeline Technology: Automated Lead Nurturing - Habel, Johannes; Hartmann, Nathaniel N.; Wiseman, Phillip; Ahearne, Michael J.; Vaid, Shashank (Journal of Marketing, 2025)
Many business-to-business sales firms use automated lead nurturing (ALN) systems, which track leads’ online behavior and nurture them through personalized content. ALN software providers claim that ALN improves lead conversion, but whether this benefit materializes is unclear. Therefore, this research examines ALN's effect across one qualitative and three quantitative studies. The findings indicate that ALN can provide valuable information to both sellers and leads and thereby improve the quality of salesperson–lead interactions, which in turn drives lead conversion. On average, ALN increases the probability of lead conversion between 0 (Studies 1 and 3) and 23 (Study 2) percentage points. However, these effects strongly depend on a lead's sales cycle length, expected sales volume, and preexisting relationship with the seller. Thereby, this article conducts the first rigorous fact-check of ALN and provides evidence that understanding the effect of ALN requires a contingency view. The findings also call on practitioners to change their current practices related to ALN. Rather than accepting industry claims at face value, practitioners should verify whether ALN improves lead conversion in their specific context. Furthermore, they should employ ALN particularly for leads where information asymmetry persists and is unlikely to be resolved through other, more costly means.